Respuesta :
y = −2x + 1
4x + 2y = −1
Replace Y in the second equation with the value of Y in the first one.
4x + 2(-2x +1) = -1
Distributive Property:
4x + -4x + 2 = -1
Combine like terms:
2 = -1 which is not true, so there are no solutions.
Answer:
Option 3 - No solution
Step-by-step explanation:
Given : The system of equations
[tex]y=-2x+1[/tex] and [tex]4x+2y=-1[/tex]
To find : Solve the system of equations using substitution ?
Solution :
Let [tex]y=-2x+1[/tex] .....(1)
[tex]4x+2y=-1[/tex] ......(2)
Substitute the value of y from equation (1) in equation (2),
[tex]4x+2(-2x+1)=-1[/tex]
[tex]4x-4x+2=-1[/tex]
[tex]2\neq -1[/tex]
As it is not true.
The solution of system does not exist i.e. no solution.
Therefore, option 3 is correct.